Chaotic and AES cryptosystem for satellite imagery - Muhaya, Fahad T. Bin (Telecommunication systems, 2013)
The rapid development, advancement, and growing use of satellite imagery and information technologies have made the security of data storage and transmission essential to prevent unlawful, unofficial, unauthorized, and illegal use/access. This paper proposes a secure satellite image encryption technique based on chaotic and Advanced Encryption Standard (AES) techniques to protect critical and confidential satellite imagery. Arnold’s cat map is used to shuffle the pixel values. A chaotic Henon map is used to generate a random sequence for the AES algorithm, and the shuffled-image is encrypted using the AES algorithm. The security and performance is acceptable to deal with high resolution and multi-spectral satellite imagery. The experimental results are shown, along with those for some traditional encryption techniques, for a comparison and evaluation. Detailed experimental results are also given of the security, statistical, and performance analyses of the complete implementation of the new proposed solution. The proposed technique presents numerous interesting and attractive features, including a high level of security, sufficiently large key-space with improved key sensitivity, pixel distributing uniformity, and acceptable speed.